Developmental Transcriptome Profiling of the Tibial Reveals the Underlying Molecular Basis for Why Newly Hatched Quails Can Walk While Newly Hatched Pigeons Cannot - Wu, Qifan; Liu, Hehe; Yang, Qinglan; Wei, Bin; Wang, Luyao; Tang, Qian; Wang, Jianmei; Xi, Yang; Han, Chunchun; Wang, Jiwen; Li, Liang (Frontiers in Cell and Developmental Biology, 2022)
Birds can be classified into altricial and precocial species. The hatchlings of altricial birds cannot stand, whereas precocial birds can walk and run soon after hatching. It might be owing to the development of the hindlimb bones in the embryo stage, but the molecular regulatory basis underlying the divergence is unclear. To address this issue, we chose the altricial pigeon and the precocial Japanese quail as model animals. The data of tibia weight rate, embryonic skeletal staining, and tibia tissues paraffin section during the embryonic stage showed that the Japanese quail and pigeon have similar skeletal development patterns, but the former had a faster calcification rate. We utilized the comparative transcriptome approach to screen the genes and pathways related to this heterochronism. We separately analyzed the gene expression of tibia tissues of quail and pigeon at two consecutive time points from an inability to stand to be able to stand. There were 2910 differentially expressed genes (DEGs) of quail, and 1635 DEGs of pigeon, respectively. A total of 409 DEGs in common in the quail and pigeon. On the other hand, we compared the gene expression profiles of pigeons and quails at four time points, and screened out 8 pairs of expression profiles with similar expression trends but delayed expression in pigeons. By screening the common genes in each pair of expression profiles, we obtained a gene set consisting of 152 genes. A total of 79 genes were shared by the 409 DEGs and the 152 genes. Gene Ontology (GO) analysis of these common genes showed that 21 genes including the COL gene family (COL11A1, COL9A3, COL9A1), IHH, MSX2, SFRP1, ATP6V1B1, SRGN, CTHRC1, NOG, and GDF5 involved in the process of endochondral ossification. These genes were the candidate genes for the difference of tibial development between pigeon and quail. This is the first known study on the embryo skeletal staining in pigeon. It provides some new insights for studying skeletal development mechanisms and locomotor ability of altricial and precocial bird species.